Tribology Behavior of In-Situ FDM 3D Printed Glass Fibre-Reinforced Thermoplastic Composites - Liow, Yu Heng; Ismail, Khairul Izwan; Yap, Tze Chuen (Journal of Research Updates in Polymer Science, 2024)
Fused deposition modeling (FDM) 3D-printed parts are generally weaker compared to injection-moulded parts. Fibre reinforcement is one of the techniques used to enhance the mechanical strength and the tribological behavior of the FDM-printed parts. Recently, a new method for creating FDM 3D-printed composites was developed. Current work focuses on the tribological behavior of the glass fibre-reinforced PLA, manufactured using this new composite manufacturing method. Experiments were conducted to investigate the effect of Glass Fibre (GF) reinforcement on FDM 3D-printed thermoplastic composites, specifically polylactic acid (PLA) under different linear sliding speed and directions. All 3D printed glass fibre-reinforced PLA (PLA-GF) composites exhibited a lower wear rate and a higher friction coefficient compared to 3D printed PLA. Increasing in disc’s linear speed or sliding speed of the pins resulted in a lower coefficient of friction and wear rate. In addition, a perpendicular raster direction towards the disc rotation or pin motion experienced greater friction and greater wear.